Citizen science substantiates jellyfish occurrence in the Mediterranean Sea - Serena Zampardi; Priscilla Licandro; Giacomo Milisenda; Danilo Scannella; Stefano Piraino; Ferdinando Boero (Scientific Reports)
Abstract In recent decades, gelatinous plankton blooms have attracted media attention due to their damaging effects on fisheries, aquaculture, tourism, human health and power/desalination plants. The scientific community often failed to recognize the rise of jellyfish, due to difficulties in monitoring their appearances and disappearances. In Italian waters, a citizen science approach was employed to monitor the presence and distribution of gelatinous zooplankton over wide spatio-temporal scales. From 2009 to March 2016, citizens identified 27 jellyfish taxa and documented their geographical distribution and seasonal occurrence across the Italian Seas. The main blooming species was Pelagia noctiluca (30% of total sightings), mainly distributed in the western Mediterranean, followed by Rhizostoma pulmo (28% of total sightings), showing a more widespread distribution. Mnemiopsis leidyi, the main Non-Indigenous Species (NIS), initially reported in the western Mediterranean, since 2016 expanded its distribution to the east. Jellyfish blooms were recorded year-round, mainly between late spring and autumn. Jellyfish hotspots were identified in the northern and southern Tyrrhenian, Ligurian Sea, and northern Adriatic regions. Citizen Science enables the detection of phenomena that can be studied more in-depth by professional scientists, leading to the discovery of previously unknown species and a better understanding of the occurrence of bloom events.